Dampak Penggunaan Gadget Terhadap Kesehatan Mata Remaja - Alisyahbana, Adam Trojan (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
The use of gadgets covers every age group of society, including children, teenagers, adults and the elderly. Of each of these groups, the percentage of gadget users among teenagers is the largest, namely 98.20%, which means that almost all teenagers in Indonesia use gadgets in their daily lives. Excessive use of gadgets will have a negative impact on teenagers, one of which is a decrease in eye health caused by staring at gadget screens too often. This research aims to examine the results of Indonesian language research on the impact of gadget use on adolescent eye health. The method used in this research is a literature review, where the literature search was carried out via Google Scholar. The keywords used in Indonesian are "eye health" and "teenagers." Meanwhile, the keywords used in English are "gadget", "eye health" and "teenager". From the results of the study carried out, it can be concluded that there are 4 journals discussing the relationship between gadget use and eye health in adolescents, namely pupils and students at several schools and universities, and 1 journal analyzes the impact of gadget use on reducing visual acuity. The use of gadgets will have a positive impact on teenagers if they are able to use gadgets according to their function and needs, however, the use of gadgets also has a negative impact on teenagers if they are not used wisely and can even cause dependency if gadgets are used for an excessive period of time.